Critical success factors of green supply chain management: case evidence of a Malaysian automotive manufacturer / Noor Sufiawati Khairani …[et al.] - Khairani, Noor Sufiawati; Kasim, Eley Suzana; Rajamanoharan, Indra Devi; Misman, Faridah Najuna (Universiti Teknologi MARA Cawangan Selangor, 2017)
This study examines the critical success factors (CSFs) of green supply chain management (GSCM) practices in the Malaysian automotive industry. Proponents of supply chain management (SCM) suggest that understanding the CSFs of SCM practices allows firms to realize supply chain benefits. However, few researchers consider the environmental aspects while discussing the CSFs of SCM, particularly in the automotive industry, the focus of this study. Despite the plethora of CSFs of SCM suggested in the literature, it is still unclear whether the identified CSFs of SCM lead to similar resulting benefits within the GSCM environment. This paper therefore contributes to filling these gaps by examining the CSFs of GSCM practices in the automotive industry in Malaysia. The study adopts a single case study method, with data collected through semi-structured interviews, observation and document reviews from an automotive manufacturing firm operating in Malaysia. Consistent with the literature, our findings indicate that the CSFs which consist of generic CSFs for SCM and GSCM-related CSFs represent the main pre-requisites for the success of green automotive SCM practices.